DHA- rich fish oil improves complex reaction time in female elite soccer players - Guzman, J. F.; Esteve, H.; Pablos, C.; Pablos, A.; Blasco, C.; Villegas, J. A. (Journal of Sports Science & Medicine, 2011)
Omega-3 fatty acids (n-3) has shown to improve neuromotor function. This study examined the effects of docosahexaenoic acid (DHA) on complex reaction time, precision and efficiency, in female elite soccer players. 24 players from two Spanish female soccer Super League teams were randomly selected and assigned to two experimental groups, then administered, in a double-blind manner, 3.5 g/day of either DHA-rich fish oil (FO =12) or olive oil (OO = 12) over 4 weeks of training. Two measurements (pre- and post-treatment) of complex reaction time and precision were taken. Participants had to press different buttons and pedals with left and right hands and feet, or stop responding, according to visual and auditory stimuli. Multivariate analysis of variance displayed an interaction between supplement administration (pre/post) and experimental group (FO/OO) on complex reaction time (FO pre = 0.713 ± 0.142 ms, FO post = 0.623 ± 0.109 ms, OO pre = 0.682 ± 1.132 ms, OO post = 0.715 ± 0.159 ms; p = 0.004) and efficiency (FO pre = 40.88 ± 17.41, FO post = 57.12 ± 11.05, OO pre = 49.52 ± 14.63, OO post = 49. 50 ± 11.01; p = 0.003). It was concluded that after 4 weeks of supplementation with FO, there was a significant improvement in the neuromotor function of female elite soccer players.